Curcumin reduces inflammation in mice with the psoriasis model by inhibiting NLRP3 inflammatory bodies - Zhang, Jiancheng; Ma, Yu; Li, Wen (Cellular and Molecular Biology, 2022)
As a chronic skin disease, psoriasis is a relatively common disease among various types of skin diseases. Because this disease is often distributed throughout the patient's body and is prone to develop, it is difficult to guarantee the quality of life and physical and mental health of patients with this disease. The purpose of this article is to investigate whether curcumin can effectively inhibit the NLRP3 inflammatory body and thereby reduce the inflammation in the mouse psoriasis model. Through the use of the curcumin gel prepared and the mouse psoriasis model, the percutaneous administration was used to investigate the mechanism and mechanism of curcumin's effect on reducing inflammation in the mouse psoriasis model. In addition, in order to better explore the curative effect of curcumin on psoriasis, related experiments were conducted by setting up a control group and an experimental group. The results show that curcumin has a good inhibitory effect on NLRP3 inflammatory bodies. Curcumin can not only reduce the NLRP3 expression and inhibit the inflammation caused by IL-22 and IL-18 but also reduce the damage of psoriasis. 22 Induced phosphorylation of STAT3 almost completely inhibits phosphorylation in normal cells. Among them, curcumin inhibited IL-22-induced phosphorylation of STAT3 up to 95.6%, and inhibited IL-22 and IL-18 by about 47%.